The Long-Term Development of Transport Emissions in the Czech Republic - Antonová, Barbora (Kaunas University of Technology, 2018)
Transport is an important element of sustainability but, on the other hand, it causes congestion, accidents, smell, noise, air pollution, health effects etc. This article will focus on the environmental pillar of sustainable transport, specifically on transport emissions. The aim of this paper is to analyze the long-term development of greenhouse gas emissions from transport in the Czech Republic. The paper shows not only trends from last years but although prediction over next five decades will be show in the paper. The long-term development is then compared with the goals of EU transport policy.
Dlouhodobý vývoj dopravních emisí v České republice
Keywords: transport; greenhouse gases; sustainable development; doprava; skleníkové plyny; udržitelný rozvoj